Meningkatkan Sumber Daya Manusia dalam Penangkalan Berita Hoaks di Media Sosial Melalui Literasi Digital - Pusporini Palupi Jamaludin; Elizabeth Tika Kristina H; Paringsih Paringsih; Laura Komala (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The aim of the Community Service Activities is to implement one of the Tri Darmas of Higher Education which is carried out by Pamulang University lecturers and students with the title "increasing human resources in preventing hoax news on social media through digital literacy" One of the abilities that every human being must have is the ability to read. This is because someone who has literacy skills will find it easy for that person to solve problems or find a solution to a problem wisely. Media literacy is an effective step to anticipate the spread of Hoks which is growing rapidly in society.This PKM was carried out on the target group of young people studying at Bambu Apus Pamulang. This PKM was carried out using a lecture method, asking questions and answers to the participants. With this service activity, these Koran students get the information they need to be able to more easily and quickly differentiate between truth and error in information. Apart from that, it can also help the general public in maintaining the information circulating in a real form